2019
DOI: 10.1108/srj-09-2018-0243
|View full text |Cite
|
Sign up to set email alerts
|

A bibliometric analysis of employee-centred corporate social responsibility research in the 2000s

Abstract: Purpose This paper aims to study the knowledge development and research dissemination on employee-centred CSR research through a social network approach by adopting bibliometric analysis. Design/methodology/approach By using the bibliometric data obtained from Scopus, descriptive analysis using social network analysis together with visualisation tool to examine the knowledge development and research dissemination on employee-centred CSR. The publications were identified by limiting search in Scopus database … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 37 publications
(39 reference statements)
0
37
0
4
Order By: Relevance
“…Diğer kaynaklar ise yüksek lisans ve doktora tezleri, web sayfaları, kurum yayınları, gazete ve dergiler, konferans bildirileri, üniversite yayınları ve araştırma proje raporlarıdır. Tüm referanslar arasında bilimsel makalelerin birincil kaynak olarak tercih edilmesi durumu internet ortamındaki zengin ve erişimi kolay literatür ile (Aguinis ve Glavas, 2012;Dabic vd., 2016;Feng vd., 2017;Bartolacci vd., 2020;Low ve Siegel, 2020;Ye vd., 2020). Ancak Türkiye'deki doktora tezlerinde atıf alan kaynakların incelendiğinde Journal of Business Ethics dergisi dışında ifade edilen sosyal sorumluluk dergilerine düşük sayıda atıf yapılmıştır.…”
Section: Sonuçunclassified
See 1 more Smart Citation
“…Diğer kaynaklar ise yüksek lisans ve doktora tezleri, web sayfaları, kurum yayınları, gazete ve dergiler, konferans bildirileri, üniversite yayınları ve araştırma proje raporlarıdır. Tüm referanslar arasında bilimsel makalelerin birincil kaynak olarak tercih edilmesi durumu internet ortamındaki zengin ve erişimi kolay literatür ile (Aguinis ve Glavas, 2012;Dabic vd., 2016;Feng vd., 2017;Bartolacci vd., 2020;Low ve Siegel, 2020;Ye vd., 2020). Ancak Türkiye'deki doktora tezlerinde atıf alan kaynakların incelendiğinde Journal of Business Ethics dergisi dışında ifade edilen sosyal sorumluluk dergilerine düşük sayıda atıf yapılmıştır.…”
Section: Sonuçunclassified
“…Ayrıca alanda yeni olan araştırmacıların alanın yapısını hızlı bir şekilde kavramalarını da kolaylaştırmaktadır (Zupic ve Carter, 2015, s. 457). Bugüne kadar bibliyometrik analiz tekniği ile sosyal sorumluluk konularına ve araştırmalarına ilişkin yapılan çalışmalar ile; çalışanlar (Low ve Siegel, 2020), tedarik zinciri yönetimi (Feng vd., 2017), iletişim literatürü (Ji vd., 2020), tanımlar (Dahlsrud, 2006;Sarkar ve Searcy, 2016), genel literatürün incelenmesi (Aguinis ve Glavas, 2012), tarih ve gelişme (Ghobadian vd., 2015;Agudelo vd., 2019), yönetim bilimi (Lockett vd., 2006, Lulewicz-Sas, 2017, sektör (Dabic vd., 2016), sürdürülebilir gelişme (Ye vd., 2020), küçük ve orta büyüklükteki işletmeler (Vázquez-Carrasco ve López-Pérez, 2013;Ortiz-Avram vd., 2018, Bartolacci vd., 2020, insan kaynakları (Stefano vd., 2018) gibi birçok konulara ilişkin sistematik açıklamalar yapılmıştır.…”
Section: Introductionunclassified
“…The development trend of any academic research is often indicated by the quantity of published research (Low and Siegel 2019). Figure 1 indicates how the publications in this field began in the early 21st century.…”
Section: Initial Data Statisticsmentioning
confidence: 99%
“…According to Del Baldo (2019), the improvement of a socially responsible commitment, with corporate social responsibility practices and the creation of a public benefit, as well as improvements in accountability, transparency, and stakeholder engagement, optimize social actions. Social actions can act as a catalyst to deal with pressing social problems that, if properly managed, can be transformed into large-scale social opportunities (Rake and Grayson, 2009;Low and Siegel, 2019).…”
Section: Eco-innovation and Social Actionsmentioning
confidence: 99%